2003
DOI: 10.1242/jcs.00716
|View full text |Cite
|
Sign up to set email alerts
|

Merotelic kinetochore orientation occurs frequently during early mitosis in mammalian tissue cells and error correction is achieved by two different mechanisms

Abstract: SummaryMerotelic kinetochore orientation occurs frequently during early mitosis in mammalian tissue cells and error correction is achieved by two different mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
313
3
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(331 citation statements)
references
References 54 publications
10
313
3
5
Order By: Relevance
“…MCAK inhibition results in merotelic attachments of kinetochores , which may reduce the number of MTs per K-fiber either directly by error correction mechanisms contributing to the release of kinetochore-MTs, or by the aberrant binding sites caused by the merotelic attachments (Cimini et al, 2003;Salmon et al, 2005), which may limit the number of end-on binding sites for MTs. The reduction in interkinetochore distance is consistent with our previous findings (KlineSmith et al, 2004), but different from that reported by others .…”
Section: Control Of Kinetochore Mt Dynamicsmentioning
confidence: 99%
“…MCAK inhibition results in merotelic attachments of kinetochores , which may reduce the number of MTs per K-fiber either directly by error correction mechanisms contributing to the release of kinetochore-MTs, or by the aberrant binding sites caused by the merotelic attachments (Cimini et al, 2003;Salmon et al, 2005), which may limit the number of end-on binding sites for MTs. The reduction in interkinetochore distance is consistent with our previous findings (KlineSmith et al, 2004), but different from that reported by others .…”
Section: Control Of Kinetochore Mt Dynamicsmentioning
confidence: 99%
“…Merotelic attachments form transiently in all cells (Cimini et al, 2003) (reviewed by Cimini and Degrassi, 2005;Musacchio and Salmon, 2007), but in normal conditions they are resolved by a specific pathway requiring Aurora-B and MCAK (Hauf et al, 2003;Kline-Smith et al, 2003;Knowlton et al, 2006). In RANBP1-depleted cultures, the increased frequency of lagging chromosomes and micronuclei in anaphase/telophase, with no detectable abnormalities in metaphase and an intact checkpoint response to NOC, would be compatible with an increased Journal of Cell Science 120 (21) frequency of merotelic attachments.…”
Section: Ranbp1-interfered Cells Display Segregation Defects During Mmentioning
confidence: 99%
“…In addition, evidence from budding yeast would suggest that syntelic attachments can be detected by the mitotic spindle checkpoint. 24 Finally, merotelic attachments occur frequently in early mitosis 25 and are not detected by the spindle checkpoint. [26][27][28][29][30][31] Nevertheless, many of them are corrected before anaphase onset by an Aurora B-dependent mechanism, 25,32 as discussed later.…”
Section: Kinetochore-microtubule Attachment and Accuracy Of Chromosommentioning
confidence: 99%
“…25,26,29,30 But, when sister chromatids separate at anaphase, opposing pulling forces exerted on merotelic kinetochores by microtubules to opposite poles affect anaphase A poleward movement. 26,27 Movement of merotelically oriented chromosomes away from the equator in anaphase depends on the ratio of kinetochore microtubules to the correct versus incorrect pole.…”
Section: Kinetochore-microtubule Attachment and Accuracy Of Chromosommentioning
confidence: 99%
See 1 more Smart Citation